Evaluation of the Complications Effectiveness and Frequency When Using Second-Generation Supraglottic Airways in Laparoscopic Interventions in the Trendelenburg Position - L. V. Arsentev; A. A. Andreenko; A. T. Gettuev; A. D. Halikov; V. P. Govorushkina; B. N. Bogomolov; A. G. Klimov; A. V. Shchegolev (Неотложная медицинская помощь, 2021)
Relevance. The supraglottic airways (SA) are now more and more often used as devices of the first choice for providing ventilation during surgical interventions of low trauma and duration, during laparoscopic operations as well. Nevertheless, some concerns remain about the possibility of using these devices in operations accompanied by a significant increase in intra-abdominal pressure, for example, when performing laparoscopy, especially in the Trendelenburg position.Aim of study. Comparison of the efficiency and safety of ventilation, the incidence of postoperative complications when using two different types of SA during laparoscopic surgical interventions performed in the Trendelenburg position.Material and methods. Eighty-three gynecological patients who were scheduled to undergo laparoscopic surgery in the Trendelenburg position were randomly assigned to two groups. In the 1st group, a laryngeal tube was installed for general anesthesia, in the 2nd group patients had a laryngeal mask. The adequacy of ventilation, gas exchange rates, oropharyngeal leakage pressure, rate of successful placement, mean and peak airway pressure at various stages of surgery, as well as the frequency of intra- and postoperative complications were assessed.Results. In all observations, there were normal indicators of gas exchange and capnography, no leakage of the breathing mixture from the circuit. The level of oropharyngeal leakage pressure was statistically different in the groups and was 32 (28; 35) in the 1st group and 28.5 (27; 31.8) cm of water column in the 2nd group. (p=0.007). The time to the onset of ventilation was 19s (18; 21) in the laryngeal tube group, 21s (19; 22.5) in the laryngeal mask group; statistically significant differences were not obtained by this criterion (p=0.059). The first installation attempt was successful in 40 cases (93%) in the 1st group and in 38 cases (95%) in the 2nd group; there was no significant difference in this indicator (p=0.94). The peak and mean airway pressure at the stages of surgery also did not differ. The study did not reveal such intraoperative complications as dislocation of the airway and aspiration of gastric contents. When analyzing postoperative complications, statistical differences were obtained in terms of the level of sore throat 3 hours after removal of SA. In terms of sore throat after 5 minutes, 6, 12, 24 hours, the frequency of hoarseness, no differences were found.Conclusion. 1. The use of different types of 2nd generation supraglottic airways with inflatable cuff (s) provides reliable protection of the upper airway during anesthesia and effective ventilation during laparoscopic surgery in the Trendelenburg position. 2. The laryngeal mask and laryngeal tube did not differ significantly in the frequency of successful insertion, ventilation efficiency, airway pressure levels at various stages of surgery, and the incidence of intra- and postoperative complications. 3. The use of a laryngeal tube provided a higher level of oropharyngeal leakage pressure, while the differences with the laryngeal mask for this indicator were statistically significant.